HEGEMONI EKONOMI PEDAGANG CINA TERHADAP RAKYAT SANUR DALAM TEKS NOVEL BIYAR-BIYUR RING PESISI SANUR - Ariestini, Ni Nyoman Sri (Humanis, 2013)
The study, titled "China Merchants Economic Hegemony Against People Sanur In text novel Biyar-Biyur Ring Pesisi Sanur" aims to explain and describe the economic power relations in Sanur Chinese traders contained in the text of the novel Biyar-Biyur Ring Pesisi Sanur. Novel Biyar-Biyur Ring Pesisi Sanur is one of Bali's modern literary works that Bellows Badung war. The existence of ethnic Chinese economic power relations in the days of Badung Bellows makes this novel interesting to study. This study uses sociological approach to literature that supported the theory of hegemony to study sociology literature on this literature focus more on the social aspects of the relationship of economic hegemony against the people of Sanur Chinese traders in the text of the novel. The method used in this study through three stages, namely the stage of the supply of data, data analysis stage, and the stage presentation of the results of the data analysis. At the stage of providing data used observational methods supported with techniques and methods of reading interviews with assisted techniques supported by the record and translation techniques. The next stage is the stage of data analysis used descriptive method of analysis. This study will describe the economic power relations by Chinese traders to the people who recorded the text Sanur biyar novel ring-biyur Pesisi sanur.
Keywords: Hegemony, Trade Port